A biolistic-based genetic transformation system applicable to a broad-range of sugarcane and energycane varieties. Issue 4 (2nd October 2018) - Ramasamy, Manikandan; Mora, Victoria; Damaj, Mona B.; Padilla, Carmen S.; Ramos, Ninfa; Rossi, Denise; Solís-Gracia, Nora; Vargas-Bautista, Carol; Irigoyen, Sonia; DaSilva, Jorge A.; Mirkov, T. Erik; Mandadi, Kranthi K.
ABSTRACT: Sugarcane and energycane ( Saccharum spp. hybrids) are prominent sources of sugar, ethanol, as well as high-value bioproducts globally. Genetic analysis for trait improvement of sugarcane is greatly hindered by its complex genome, limited germplasm resources, long breeding cycle, as well as recalcitrance to genetic transformation. Here, we present a biolistic-based transformation and bioreactor-based micro-propagation system that has been utilized successfully to transform twelve elite cane genotypes, yielding transformation efficiencies of up to 39%. The system relies on the generation of embryogenic callus from sugarcane and energycane apical shoot tissue, followed by DNA bombardment of embryogenic leaf roll discs (approximately one week) or calli (approximately 4 weeks). We present optimal criteria and practices for selection and regeneration of independent transgenic lines, molecular characterization, as well as a bioreactor-based micro-propagation technique, which can aid in rapid multiplication and analysis of transgenic lines. The cane transformation and micro-propagation system described here, although built on our previous protocols, has significantly accelerated the process of producing and multiplying transgenic material, and it is applicable to other varieties. The system is highly reproducible and has been successfully used to engineer multiple commercial sugarcane and energycane varieties. It will benefit worldwide researchers interested in genomics and genetics of sugarcane photosynthesis, cell wall, and bioenergy related traits.